Second order parallel tensors on S -manifolds and semi-parallel hypersurfaces of S -space forms - Belkhelfa, M.; Mahi, F. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 515.12 We study a second order parallel symmetric tensor in an S-manifold and we deduce that there is no semi-parallel hypersurface in S-space forms M^2n+s(c) with c eq s.